2003
DOI: 10.1002/chem.200390179
|View full text |Cite
|
Sign up to set email alerts
|

Getting Closer to the Real Bacterial Cell Wall Target: Biomolecular Interactions of Water‐Soluble Lipid II with Glycopeptide Antibiotics

Abstract: A novel synthesized watersoluble variant of lipid II (LII) was used to evaluate the noncovalent interactions between a number of glycopeptide antibiotics and their receptor by bioaffinity electrospray ionization mass spectrometry (ESI-MS). The water-soluble variant of lipid II is an improved design, compared to the traditionally used tripeptide, of the target molecule on the bacterial cell wall. A representative group of glycopeptide antibiotics was selected for this study to evaluate the validity of the novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…The rate of bacterial killing by nisin over the studied concentration range was satisfactorily described when modeled to be proportional to the nisin concentration, and a more complex function was not necessary to describe the profiles. This second-order killing function for nisin was in agreement with its ability to form pores in bacterial membranes (16,38). The killing rate constant was 85.5-fold lower for the Nis i and 821-fold lower for the Nis r populations compared to the Nis s populations (Table 1).…”
Section: Resultssupporting
confidence: 71%
“…The rate of bacterial killing by nisin over the studied concentration range was satisfactorily described when modeled to be proportional to the nisin concentration, and a more complex function was not necessary to describe the profiles. This second-order killing function for nisin was in agreement with its ability to form pores in bacterial membranes (16,38). The killing rate constant was 85.5-fold lower for the Nis i and 821-fold lower for the Nis r populations compared to the Nis s populations (Table 1).…”
Section: Resultssupporting
confidence: 71%
“…The solution-phase structures of complexes formed between the vancomycin-group antibiotics and several small bacterial cell-wall mimicking peptides have been elucidated using NMR spectroscopy [3, 18 -20] and X-Ray [6, 21,22]. Electrospray ionization mass spectrometry (ESI-MS) has been applied to study vancomycinpeptide complexes in gas phase [23][24][25][26][27][28][29][30][31][32]. These gas-phase ESI-MS studies have determined the stoichiometry of vancomycin complexes and relative binding affinities for D/L-peptide stereoisomers.…”
Section: Vancomycin-peptide Noncovalent Complexesmentioning
confidence: 99%
“…Vancomycin primarily interacts with the peptidic region of lipid II and the interaction between vancomycin and a range of lipid II peptidoglycan analogs has been studied using a variety of techniques. Lipid II is insoluble in water and thus most investigations of the recognition of lipid II by vancomycin have involved either chemically modified or truncated fragments of lipid II [10]. NMR and X-ray crystallographic studies [11][12][13][14][15][16][17] showed that the ligand bound to the concave (front face) of vancomycin, the C-terminal carboxylic acid group of D-Ala-D-Ala interacting with the backbone amide groups of resides NLEU1, HDPY2 and ASN3.…”
Section: Introductionmentioning
confidence: 99%